2015
DOI: 10.1186/s12950-015-0049-4
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and anti-inflammatory activity of Ocimum labiatum extract and isolated labdane diterpenoid

Abstract: BackgroundPlants from the genus Ocimum are used as folk medicine for treating various diseases including inflammatory and immune-related diseases. Numerous reports have suggested plant extracts and their constituents as possible anti-inflammatory agents. Here, in vitro evidence of Ocimum labiatum’s immune-enhancing and antioxidant properties is presented for the first time.MethodsThe anti-inflammatory effect of O. labiatum ethanolic extract and an isolated diterpenoid was determined using a cytometric bead arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…In particular, ethanol and ethyl acetate extracts obtained from branches and leaves of the plant have been found to have significant antioxidant activity and high amount of phenolic contents. Phenolic compounds present in plants are known to be powerful antioxidants [19]. Also, in the phytochemical studies on different parts of the plant, it have been reported that this species contained phenolic compounds such as flavonoids and tannins intensively.…”
Section: Discussionmentioning
confidence: 98%
“…In particular, ethanol and ethyl acetate extracts obtained from branches and leaves of the plant have been found to have significant antioxidant activity and high amount of phenolic contents. Phenolic compounds present in plants are known to be powerful antioxidants [19]. Also, in the phytochemical studies on different parts of the plant, it have been reported that this species contained phenolic compounds such as flavonoids and tannins intensively.…”
Section: Discussionmentioning
confidence: 98%
“…Anti-inflammatory effect of Ocimum labiatum ethanolic extract and an isolated diterpenoid was determined using a cytometric bead array technique. 25 μg/mL noncytotoxic concentration of O. labiatum extract significantly (p<0.05) inhibited the production of pro-inflammatory cytokines; IL-2, IL-4, IL-6, and IL-17A [14]. Free steroids, saponin contents of crude extract from leaves of Scutellaria agrestis showed significant analgesic effect and the anti-inflammatory doses of 30, 100, and 300 mg/kg of the formalin test [15].…”
Section: Boswellia Ovalifoliolatamentioning
confidence: 89%
“…Ethanol extract from Vernonia polyanthes leaves at doses of 200 and 400 mg/kg, administered 4 h before the carrageenan injection, significantly reduced the exudate volume (29.25% and 45.74%, respectively) and leukocyte migration (18.19% and 27.95%, respectively) [21]. Lindenanesesquiterpenoid (14) dimer, shizukaols B and D were isolated from the whole plant of Chloranthus serratus. The compound showed significant anti-inflammatory activities with IC50 values of 0.22, 0.15, and 7.22 μM, respectively [22].…”
Section: Boswellia Ovalifoliolatamentioning
confidence: 99%
“…Terpenoids are important phytochemicals that have significant antioxidant and anti-inflammatory potentials [26,27]. Alkaloids have also been demonstrated to scavenge diphenyl-2-picrylhydrazyl and 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) radicals, reduce cupric ions attributed to the ability of the pyrrole nitrogen to form an iminoquinone structure by donating either a hydrogen or electrons to the free radicals [28].…”
Section: Discussionmentioning
confidence: 99%